Alpha Particles in Effective Field Theory - Barros, Cristian Javier Caniu (2014)
In this thesis we work on the problem of the two-alpha-particle system using a halo/- cluster effective field theory (EFT). Our goal is to address the alpha-alpha scattering observables and its low-energy resonance identified as the ground state of Beryllium-8. In this work we start with an EFT in which the degrees of freedom are the alpha particles interacting via momentum-dependent contact forces. These, in contrast to forces that are energy-dependent, are more useful in extending the theory to systems with more than two alpha particles. Additionally, momentum-dependent forces allow us to address causal restrictions on scattering observables, known as the Wigners causality bound. We present our EFT calculations for the alpha-alpha system.